COVARAGE OF THE IMAGE OF A HISTORICAL FIGURE IN THE WORKS OF KHAYRIDDIN SULTANOV (Scientific journal of the Fergana State University, 2023)
The article deals with the artistic images and interpretations of historical figures in the works of Khayriddin Sultanov.